The effectiveness of generating interactions between schemata and text (gist) strategy towards the students' writing skill in Indramayu - Indra Yoga Prawiro; Siska Nurhasanah (Journal of Research on English and Language Learning (J-REaLL), 2021)
Many students have difficulties in writing the text. Some of the problems in writing such as the difficulties in expressing their idea into the words, time consuming activities and the limited number of vocabularies. This study focused on the effectiveness of GIST (Generating Interaction between Schemata and Text) strategy in improving students' writing skill at the second grade of SMK Negeri 1 Sindang. The GIST is strategy for taking notes while the students are reading and writing good summaries. This strategy works on many levels, this allows students to put concept into their own words. This activity helps teachers and students to identify key concept. By using quasi-experimental method non-equivalent design, the instruments of this research were pre-test and post-test. The participants of the research were class XI TOI 1 and XI TOI 2 of first semester in SMK Negeri 1 Sindang. Each class consisted of 33 students. The statistical analysis showed the value of Tobs was 2.23 while the value of Ttable was 1.669 which means Tobs was higher than Ttable 2.23>1.669 (Tobs>Ttable). It means that the GIST strategy is effective in teaching and learning writing especially in report text.